Relationship between quality of professional capacity building for kindergarten teachers and children’s language development: the mediating role of kindergarten language education activities quality - Wu, Qiong; Wang, Guoxia; Li, Chang (Frontiers in Psychology, 2023)
Strengthening the professional capacity building for kindergarten teachers is crucial for improving the quality of kindergarten education and promoting children’s development. In order to explore the impact of the quality of professional capacity building for kindergarten teachers and kindergarten language education activities quality on children’s language development, a study was conducted. A total of 1584 children from 90 kindergartens in 5 provinces in China were randomly selected as research participants. Utilizing an independent sample t-test and correlation analysis (with SPSS 26.0 as the tool), the study analyzed the disparities in the professional capacity building for kindergarten teachers of different types, kindergarten language education activities quality, and the children’s language developmental levels, as well as the interrelationships among these factors. A multilevel structural equation model (using MPLUS 8.3 as the tool) was employed to analyze the mediating role that the kindergarten language education activities quality plays between the quality of professional capacity building for kindergarten teachers and children’s language development levels. The results indicate that children in public kindergartens demonstrate significantly higher language development levels than those in private kindergartens. A positive correlation exists between the quality of professional capacity building for kindergarten teachers, kindergarten language education activities quality and children’s language development levels. Furthermore, kindergarten language education activities quality shows partial mediating effects on the relationship between them. These findings highlight the need to enhance the quality of education in private kindergartens, reduce the disparities in language development levels between private and public kindergartens, and reinforce the quality of professional capacity building for kindergarten teachers to provide effective support for children’s language development. Ultimately, the study suggests concentrating on the organization and implementation of kindergarten language education activities as a means of evaluating the quality of professional capacity building for kindergarten teachers.